TIME OF FLOODING FOR GOGO RANCAH RICE AND REPRODUCTIVE STAGE MOISTURE STRESS FOR WALIK JERAMI RICE - Didiek Setio Budi; Bambang Suprihatno (Agromet, 1994)
Abstract is available in the full text (pdf format)